Everyone Talks Everything With ChatGPT: Students' Uses of ChatGPT and Their Impact on Learning Performance - Petrič, Gregor (International journal of technology and human interaction, 2024)
Research suggests that ChatGPT offers numerous affordances for students, who use it for various purposes, yet the field lacks quantitative studies that offer insight into a variety of students' actual uses of ChatGPT and their impact on academic performance. The main aims of this paper were (a) to introduce and validate a typology of students' ChatGPT uses, (b) to identify clusters of students with similar patterns of ChatGPT uses, and (c) to investigate the impact of ChatGPT uses on academic performance. An online survey research was conducted, which resulted in a typology of 10 distinct uses of ChatGPT and four distinct clusters of students. The strongest predictor of academic performance is information searching and explanation. Problematic use of ChatGPT, while resulting in improved grades, is found to be detrimental to competencies. Although the study might not fully represent the diversity of students' experiences across academic institutions, the typology offers a baseline for nuanced research and interventions pertaining to particular ChatGPT uses among students.